The Influence of Visionary Leadership, Organizational Culture, and Work Discipline on Employee Performance at SMP Negeri 1 Kedungwaringin - Aji Mulyadin; Sonny Hersona; Hartelina Hartelina (Dinasti Publisher, 2023)
This study has purpose in determining the correlation between visionary leadership, organizational culture, and work discipline in influencing the performance of employees at SMPN 1 Kedungwaringin Bekasi Regency. This research method applies empirical quantitative research through verifiative descriptive approach. The population and sample used amounted to 64 respondents consisting of 59 teachers and 5 education staff. The results of this research indicate that visionary leadership, organizational culture, and work discipline had significantly positive effect on the performance of employee. In addition, vision leadership, organizational culture, as well as work discipline also had simultaneous effect on the performance.